Daya Tarik Sektor Unggulan Antar Kota/Kabupaten di Kalimantan Utara - Joseph Manganju Sitorus (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
This study determine the development of North Kalimantan after separated from East Kalimantan through leading sectors and attractiveness between cities/regencies. We use Location Quotient (LQ) analysis to determine the leading sector Gravity Model to determine the attractiveness of each cities/regencies in North Kalimantan. The results of the study find each city and regency in North Kalimantan has unique leading sector the different each other. Meanwhile, based on Gravity Model, we find that Tarakan City has the greatest attraction.